PENINGKATAN HASIL BELAJAR IPA MATERI PERKEMBANGBIAKKAN VEGETATIF TUMBUHAN DENGAN QUANTUM TANDUR DI SDN 3 KRACAK KABUPATEN BANYUMAS - Riski Nurseptyani (STKIP Melawi, 2022)
Abstract: This research aims to improve science learning outcomes, especially in the material of vegetative propagation of plants. The research was conducted in class VI B SDN 3 Kracak with 24 students as research subjects. This research lasted for 2 cycles using the classroom action research method. The results showed an increase in student learning outcomes, seen from the learning outcomes of pre-cycle, cycle I, and cycle II. The average student learning outcomes in pre-cycle is 35,50. After learning with the Quantum TANDUR method, in cycles I and II the researcher carried out learning activities in the form of apperceptions to foster students' interest in learning, learning activities outside the classroom, delivering material via video, quizzes on matching plants and how to reproduce them, quizzes using the quiziz application, and giving awards to students who are active in learning, there is an increase in the first cycle of 25.38 with an average value of 60.88. Furthermore, in cycle II, there was an increase of 16.91 with an average value of 77.71. Thus, the success criteria in this study have been achieved, because as many as 83.3% of students have obtained grades/learning outcomes above the Minimum Completeness Criteria. Keywords: learning outcomes, vegetative reproduction of plants, Quantum TANDUR Abstrak: Penelitian ini bertujuan meningkatkan hasil belajar IPA khususnya pada materi perkembangbiakkan vegetatif pada tumbuhan. Penelitian dilaksanakan di kelas VI B SDN 3 Kracak dengan subyek penelitian sebanyak 24 siswa. Penelitian ini berlangsung selama 2 siklus dengan menggunakan metode Penelitian Tindakan Kelas (PTK). Hasil penelitian menunjukan adanya peningkatan hasil belajar siswa, dilihat dari hasil belajar pra siklus, siklus I, dan siklus II. Rata-rata hasil belajar siswa pada prasiklus adalah 35,50. Setelah dilakukan pembelajaran dengan metode Quantum TANDUR, dimana pada siklus I dan II peneliti melakukan kegiatan pembelajaran berupa apersepsi untuk menumbuhkan minat belajar siswa, kegiatan pembelajaran di luar kelas, penyampaian materi melalui video, kuis menjodohkan tumbuhan dan cara perkembangbiakkannya, kuis menggunakan aplikasi quiziz, serta pemberian penghargaan pada siswa-siswa yang aktif dalam pembelajaran, terlihat adanya peningkatan pada siklus I sebanyak 25,38 dengan nilai rata-rata 60,88. Selanjutnya pada siklus II kembali terjadi peningkatan sebanyak 16,91 dengan nilai rata-rata menjadi 77,71. Dengan demikian kriteria keberhasilan pada penelitian ini telah tercapai, karena sebanyak 83,3% siswa telah memperoleh nilai/hasil belajar di atas Kriteria Ketuntasan Minimal (KKM). Kata Kunci: hasil belajar, perkembangbiakkan vegetatif tumbuhan, Quantum TANDUR.